2023
DOI: 10.1530/erc-23-0102
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangioleiomyomatosis: where endocrinology, immunology and tumor biology meet

Abstract: Lymphangioleiomyomatosis (LAM) is a cystic lung disease found almost exclusively in genetic females and caused by small clusters of smooth muscle cell tumors containing mutations in one of the two tuberous sclerosis genes (TSC1 or TSC2). Significant advances over the past 2-3 decades have allowed researchers and clinicians to more clearly understand the pathophysiology of LAM, and therefore better diagnose and treat patients with this disease. Despite substantial progress, only one proven treatment for LAM is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Many studies have shown that estrogen is an important factor in LAM cell proliferation, migration, and metastasis. Due to the coexpression of smooth muscle proteins (actin and desmin) and melanocyte markers (HMB-45, Melan-A, and MART-1), LAM cells are thought to derive from perivascular epithelial cells, although this is still unclear [1,9,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that estrogen is an important factor in LAM cell proliferation, migration, and metastasis. Due to the coexpression of smooth muscle proteins (actin and desmin) and melanocyte markers (HMB-45, Melan-A, and MART-1), LAM cells are thought to derive from perivascular epithelial cells, although this is still unclear [1,9,14].…”
Section: Discussionmentioning
confidence: 99%
“…Disease progression occurs during periods with high estrogen concentrations, e.g., during pregnancy or hormonal therapy, while the development of symptoms declines after menopause. Some studies suggest that antiestrogen therapy could be a recognized treatment of LAM [1,7,14]. Reports on treatment with gestagens and estrogen receptor modulators are unclear and require further research.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that estrogen is an important factor in LAM cell proliferation, migration, and metastasis. Due to the co-expression of smooth muscle proteins (actin and desmin) and melanocyte markers (HMB-45, Melan-A, and MART-1), LAM cells are thought to derive from perivascular epithelial cells, although this is still unclear [1,8,11].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with confirmed LAM should be treated with an mTOR inhibitor, sirolimus, or everolimus [2,11].…”
mentioning
confidence: 99%
See 1 more Smart Citation